KONSEP PRAKTIK MANAJEMEN LABA DALAM PERSEPSI ETIS MAHASISWA (Studi Kasus Pada Universitas XYZ) - Islamiah Kamil (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2017)
This study aims to determine and measure the Effect of Ethical Perceptions of Accounting Lecturers, Management Lecturers, Accounting Students and Management Students in the Faculty of Economics and Business of XYZ University Against Profit Management Practices. The research method used is causal, with analysis unit of Accounting Lecturer, Management Lecturer, Accounting Student and Management Student in Faculty of Economics and Business Universitas XYZ, Data analysis is done by descriptive analysis and simple linear regression test. The result of research shows from regression test result Simple linear there is a positive influence Ethical Perceptions Lecturer Accounting, Lecturer Management and Accounting Students Faculty of Economics and Business University XYZ Against Profit Management Practice. Therefore, the more understood Lecturer Accounting, Lecturer Management and Accounting Students to earnings management practices then the more positive ethical perceptions of earnings management practices. While on Variable Perception of Student Ethical Management There is no positive influence of Student Ethical Perception of Management Faculty of Economics and Business of XYZ University Against Profit Management Practice. This indicates that the less understanding of management students to the practice of earnings management, the ethical perception is also more negative to the practice of earnings management.